Experimental and computational study on rock bolt modelling and its application on a new type of energy-absorbing rock bolt - Yokota, Yasuhiro (2019)
Recently, conventional tunnelling methods (or the drill & blasting tunneling methods, the new Austrian tunneling methods) have been frequently applied to tunnels/caverns under severe geological conditions. Under such adverse conditions, it is a concern that tunnel support materials might fail because of the huge ground pressure and large tunnel deformation. As a result, the tunnel may lose its stability due to decreased effectiveness of tunnel supports. Therefore, essential components of tunnel supports (e.g., rock bolts) are becoming more important. According to the previous studies, the interface behaviour between the rock bolt and the bond material (i.e., the debonding process along the interface and crack propagation in the bond material) is recognised as one of the most important factors significantly affecting the reinforcement effects of rock bolts. However, there is little information available on the detailed interface behaviour. This research aims to investigate the interface behaviour via both laboratory tests (shear test) and numerical simulations using the discontinuous deformation analysis (DDA). As a results, it can be found that the DDA is an effective tool reproducing the accurate interface behaviour, and therefore the simulation results enable us to better understand the bolt-grout interface behaviour in detail. Based on the accurate DDA rock bolt model, a new energy-absorbing rock bolt was designed. This rock bolt has high loading capacity and large deformability. Moreover, it can control the ultimate tunnel deformation utilizing the specially designed anchor. By carrying out the DDA-based simulations of pull-out tests and tunnel excavation, the reinforcement effect of the newly-developed rock bolt was investigated. As a result, it can be concluded that the new rock bolt has a significant advantage over the widely-used fully grouted rock bolt when the large tunnel displacement occurs.